Brain mechanisms underlying reactive aggression in borderline personality disorder - sex matters - Herpertz, Sabine; Nagy, Krisztina; Ueltzhöffer, Kai; Schmitt, Ruth; Mancke, Falk; Schmahl, Christian; Bertsch, Katja (Biological psychiatry, 2017)
Background: Aggression in borderline personality disorder (BPD) is thought to be mediated through emotion dysregulation via high trait anger. Until now, data comparing anger and aggression in female and male patients with BPD have been widely missing on the behavioral and particularly the brain levels. Methods: Thirty-three female and 23 male patients with BPD and 30 healthy women and 26 healthy men participated in this functional magnetic resonance imaging study. We used a script-driven imagery task consisting of narratives of both interpersonal rejection and directing physical aggression toward others. Results: While imagining both interpersonal rejection and acting out aggressively, a sex × group interaction was found in which male BPD patients revealed higher activity in the left amygdala than female patients. In the aggression phase, men with BPD exhibited higher activity in the lateral orbitofrontal and dorsolateral prefrontal cortices compared with healthy men and female patients. Positive connectivity between amygdala and posterior middle cingulate cortex was found in female patients but negative connectivity was found in male patients with BPD. Negative modulatory effects of trait anger on amygdala-dorsolateral prefrontal cortex and amygdala-lateral orbitofrontal cortex coupling were shown in male BPD patients, while in female patients trait anger positively modulated dorsolateral prefrontal cortex-amygdala coupling. Trait aggression was found to positively modulate connectivity of the left amygdala to the posterior thalamus in male but not female patients. Conclusions: Data suggest poor top-down adjustment of behavior in male patients with BPD despite their efforts at control. Female patients appear to be less aroused through rejection and to successfully dampen aggressive tension during the imagination of aggressive behavior.